2017
DOI: 10.1002/jhbp.522
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of surgical outcomes between open and robot‐assisted minimally invasive pancreaticoduodenectomy

Abstract: Robot PD is comparable to open PD in early outcomes. Robot PD is safe and feasible and enables early recovery; indication for robot PD is expected to expand in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Therefore, RAPD surgery is more advantageous than LPD surgery. Recent reports have shown that RAPD is safer and more efficient than LPD among properly selected patients 11,12 . Therefore, RAPD is technically a feasible alternative to the laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RAPD surgery is more advantageous than LPD surgery. Recent reports have shown that RAPD is safer and more efficient than LPD among properly selected patients 11,12 . Therefore, RAPD is technically a feasible alternative to the laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic pancreas surgery (Table 4) [24][25][26][27][28][29][30][31][32] Robotic pancreas surgery can be divided into two main groups: resection only and resection followed by reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple single or multi-institutional retrospective studies to compare specific outcomes between robotic, laparoscopic and open approaches are reported [6,[14][15][16][18][19][20][21][22][23][24] . A large systematic review examined data from 13 retrospective series [25] .…”
Section: Discussionmentioning
confidence: 99%